TEST OF FORMAL AND PHYSICAL PROPERTIES FOR PREPARATION OF TOFUMASA KOLANG-KALING SEED POWDER COMBINE (Arenga pinnata L.) CREAM SHELL - Sofia Rahmi Tambusai; Anggun Syahfitri (JBIO: jurnal biosains (the journal of biosciences), 2023)
Tofu waste is waste from the tofu processing industry that has hardly been used except as animal feed or simply thrown away. Kolang Kaling is widely used as a processed food in the community. The aim of this study was to prepare creamy peeling formulas from tofusae and kolang-kaling seeds. This study started with the preparation of tofu powder and tofu clay, then a creamy exfoliating preparation was made from the second combination in the ratio (1:1; 1:3 and 3:1). Physical testing of the cream peeling formulations was then performed in the form of organoleptic, spreadability, stickiness, cream type, protection test, pH test and preference test. The results obtained in the form of Formula I with the ratio (1:1) are the best compared to the other two formulas.